2009
DOI: 10.1016/j.tetlet.2009.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael addition of malonates to enones catalyzed by a siloxy amino acid lithium salt

Abstract: Abstract-Siloxy amino acid lithium salt, O-tert-butyldiphenylsilyl L-serine lithium salt, was found to be an effective catalyst for the asymmetric Michael addition reaction of malonates to enones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Thus adduct 8 has the S-configuration. This procedure appears, until now, the simplest available protocol in order to obtain the S-isomer of 8 [27].…”
Section: Malonates and Related 13-dicarbonylsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus adduct 8 has the S-configuration. This procedure appears, until now, the simplest available protocol in order to obtain the S-isomer of 8 [27].…”
Section: Malonates and Related 13-dicarbonylsmentioning
confidence: 99%
“…All malonates and cyclic enones react generally smoothly to generate adducts with high yields and excellent enantioselectivities, except 2-cyclopentenone, which gives 88%, 64%, 47% yield and 30%, 63%, 55% ee under Ley [21], Ye [24], and Yoshida [27] This difficulty has been overcome using a chiral diamine-acid combination catalyst in methanol [23]. At the HF/6-31G(d) level of theory, the transition states C has a minimum of energy over transition states, where methanol or malonate are not involved in hydrogen bonding with the catalyst.…”
Section: Malonates and Related 13-dicarbonylsmentioning
confidence: 99%
“…7,8 In this context, we attempted the thio-Michael addition of benzyl mercaptan with 2-cyclohexen-1-one (2a) in the presence of the catalyst 1a (Scheme 1). The reaction slowly proceeded to give the desired Michael adduct, 3-(phenylmethylthio)cyclohexanone (3a); however, the enantioselectivity was quite low (7% ee).…”
mentioning
confidence: 99%
“…Unfortunately, the reaction of 2-cyclopenten-1-one (2c) was very slow even at 37 °C (Table 4, entry 5). 7,9 As for a Michael donor, it was found that an electron-deficient mercaptan gave lower enantioselectivity. For example, the reaction of 2a with 4-chlorophenylmethyl mercaptan afforded a Michael adduct 3d with 27% ee, while 4-methoxyphenylmethyl mercaptan afforded 3e with 50% ee (Table 4, entries 6 and 7).…”
mentioning
confidence: 99%
See 1 more Smart Citation